APPLICATION OF CAR LEARNING MODEL (CLASSROOM ACTION RESEARCH) MEDIA PICTURE IN INCREASING THE LEARNING ACTIVITIES OF ELEMENTARY STUDENTS IN TENGA-TENGA VILLAGE: PENERAPAN MODEL PEMBELAJARAN CAR (CLASSROOM ACTION RESEARCH) MEDIA PICTURE DALAM MENINGKATKAN AKTIVITAS KEGIATAN BELAJAR SISWA SD PADA DESA TENGA-TENGA - Patresya Elly; Dian Soamole; Sartia Sartia; An’nissa Laras Wati; Anita Kelley; Gema Azuna; Martinus Samangun; Nurhayati Renuat; Jihan Elmira; Dedi M Pelu (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
The inefficient and effective learning process for Elementary School in the village of tenga-tenga in English learning activities, has an impact on students learning outcomes at SDN 259 Maluku Tengah which is less than optimal because, teacher is less involved in the learning and teaching process due to lack of knowledge received by students there are also no applicable activities for students to do, try, and experience the activities themselves directly. and Teacher do not really understand about various methods that can improving students learning outcomes. This article aims to make that teacher can applying this method at the Elementary School and can Improve students activities and learning outcomes In learning English by applying the CAR method of image media. In this the CAR of method is a method in where the students can Involv or interaction directly with Teacher and all the Students in the classroom. And also they do not fells bored during the English lesson. And Conclusion of this article is that by applying the image media method, it can Improving student’s ability learning outcomes in English subject of village in tenga-tenga